Halide solid electrolyte and preparation method and application thereof

By introducing a hydrophobic layer on the core surface of the halide solid electrolyte, the problem of degradation of the performance of halide electrolyte in humid environments is solved, and its air stability and circulation performance are significantly improved, and the cost is reduced.

CN119627189APending Publication Date: 2025-03-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1

Patent Information

Application Number
CN202411820511.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Halogenated electrolytes are prone to absorb moisture in humid environments, resulting in a decrease in ionic conductivity and deterioration of electrochemical properties, and are limited in applications in high humidity environments.

Method used

By introducing a dense hydrophobic layer on the surface of the core of the halide solid electrolyte, a hydrophobic layer with O=POLi covalent bond is formed by introducing a dense hydrophobic layer on the surface of the core by using a hydrophobic agent such as dicetyl phosphate to form a hydrophobic layer with O=POLi covalent bond to block the contact between the water molecules and the core.

Benefits of technology

It significantly improves the air stability of halide solid electrolytes, maintains high ion conductivity, extends the cycle life of all-solid lithium-ion batteries, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627189A_ABST
    Figure CN119627189A_ABST
Patent Text Reader

Abstract

The invention provides a halide solid-state electrolyte and a preparation method and application thereof. The halide solid-state electrolyte comprises a halide solid-state electrolyte inner core and a halide solid-state electrolyte outer core, and the hydrophobic layer is uniformly coated on the halide solid electrolyte core, and the hydrophobic layer comprises bis-hexadecyl phosphate. According to the halide solid electrolyte as well as the preparation method and the application thereof, the air stability of the halide solid electrolyte can be remarkably improved, the cycle performance of an all-solid-state lithium ion battery is improved, the manufacturing process is simple, and the cost is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly to a halide solid electrolyte, a preparation method thereof, and an application thereof. Background Art

[0002] In recent years, with the rapid development of renewable energy and portable electronic devices, the demand for lithium-ion batteries, solid-state batteries, and other electrochemical energy storage devices has increased significantly. Due to their advantages such as a wide electrochemical window, excellent thermal stability, and good mechanical properties, halide electrolytes have become one of the electrolyte materials attracting much attention in solid-state batteries and other high-performance electrochemical devices. However, due to the high hydrophilicity of halide electrolytes, halide electrolytes face the negative impact of environmental humidity on their performance in practical applications. In a humid environment, halide electrolytes are prone to absorb moisture, resulting in a decrease in ionic conductivity, deterioration of electrochemical performance, and even decomposition of halide electrolytes and destruction of the material structure, reducing the cycle life and safety of the battery and also limiting the wide application of halide electrolytes in high-humidity environments. Summary of the Invention

[0003] The present invention provides a halide solid electrolyte, a preparation method thereof, and an application thereof. By means of the halide solid electrolyte, the preparation method thereof, and the application thereof provided by the present invention, the air stability of the halide solid electrolyte can be significantly improved, the cycle performance of all-solid-state lithium-ion batteries can be enhanced, and the manufacturing process is simple and the cost is relatively low.

[0004] To solve the above technical problems, the present invention is realized through the following technical solutions.

[0005] The present invention provides a halide solid electrolyte, which at least includes:

[0006] A halide solid electrolyte core; and

[0007] A hydrophobic layer uniformly coated on the halide solid electrolyte core, and the hydrophobic layer includes bishexadecyl phosphate.

[0008] In an embodiment of the present invention, the thickness of the hydrophobic layer is 1 nm to 100 nm.

[0009] In an embodiment of the present invention, the chemical formula of the halide solid electrolyte core is Li 2+n Zr 1-n M n Cl 6-x- y Br x I y , where 0 < n ≤ 0.6, 0 ≤ x ≤ 6, 0 ≤ y ≤ 6, and x + y ≤ 6; M is selected from one or more of V, Cr, Mn, Fe, Co, or Ni.

[0010] In one embodiment of the present invention, M is selected as Fe, and the value range of n is 0.01≤n≤0.5.

[0011] The present invention also provides a method for preparing the halide solid electrolyte described above, comprising at least the following steps:

[0012] adding a hydrophobic agent into a solvent to prepare a modified solution;

[0013] soaking the halide solid electrolyte in the modified solution at a preset temperature for a first time; and

[0014] The halide solid electrolyte after soaking is taken out and dried under vacuum conditions.

[0015] In one embodiment of the present invention, the preset temperature is 0-60° C., and the first time is 0.1 h-10 h.

[0016] In one embodiment of the present invention, the solvent is selected from one or more of toluene, chlorobenzene, xylene, n-heptane, n-decane, n-hexane, glycol dimethyl ether, 1,2-ethylenediamine, ethyl acetate, benzyl acetate or butyl butyrate, the hydrophobic agent includes dihexadecyl phosphate, and the concentration of the hydrophobic agent in the modified solution is 0.01 mol / L to 0.5 mol / L.

[0017] In one embodiment of the present invention, the drying conditions include: a drying temperature of 25° C. to 300° C., and a drying time of 0.1 h to 24 h.

[0018] The present invention also provides an all-solid-state lithium-ion battery, comprising:

[0019] Positive electrode;

[0020] negative electrode;

[0021] A solid electrolyte membrane is provided between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane comprises the halide solid electrolyte described above.

[0022] The present invention also provides an electronic device comprising the above-mentioned all-solid-state lithium-ion battery.

[0023] In summary, the present invention proposes a halide solid electrolyte and its preparation method and application. By introducing the M element into the core of the halide solid electrolyte, the ionic conductivity of the halide solid electrolyte can be improved, the interface performance between the solid electrolyte membrane and the electrode can be improved, and the cost can be reduced. By introducing a dense hydrophobic layer on the surface of the halide solid electrolyte core, the contact between water molecules and the halide solid electrolyte core can be blocked, thereby significantly improving the air stability of the halide solid electrolyte. It is possible to form a halide solid electrolyte with an outer hydrophobic alkyl surface and an inner layer with high Li + The hydrophobic layer has good chemical stability and ion conductivity, which can greatly improve the stability of the halide solid electrolyte to air without significantly reducing the ion conductivity of the halide solid electrolyte, thereby improving the cycle performance of all-solid-state lithium-ion batteries. A simple immersion method can achieve a uniform hydrophobic layer coating on the surface of the halide solid electrolyte, which is simple to process and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a diagram of the 1C / 1C long cycle performance of the all-solid-state lithium-ion battery in Example 3 at room temperature. DETAILED DESCRIPTION

[0026] The following describes the embodiments of the present invention through specific examples. Those skilled in the art will readily understand the other advantages and benefits of the present invention from the disclosure herein. The present invention may also be implemented or applied through various other specific embodiments, and the details in this specification may be modified or altered based on different viewpoints and applications without departing from the spirit of the present invention.

[0027] It should be understood that the present invention can be implemented in different forms and should not be interpreted as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0028] The technical solution of the present invention is further described in detail below with reference to several embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0029] The present invention provides a halide solid electrolyte, which at least includes a halide solid electrolyte core and a hydrophobic layer. The hydrophobic layer is uniformly coated on the halide solid electrolyte core. For example, the hydrophobic layer includes dicetyl phosphate (DHP), etc. By introducing a dense hydrophobic layer on the surface of the halide solid electrolyte core, the contact between water molecules and the halide solid electrolyte core can be blocked, thereby significantly improving the air stability of the halide solid electrolyte. Moreover, the hydrophobic layer has good chemical stability and ionic conductivity to ensure that the intrinsic properties of the halide solid electrolyte are not affected.

[0030] In an embodiment of the present invention, the chemical formula of the halide solid electrolyte core is, for example, Li 2+n Zr 1-n M n Cl 6-x- y Br x I y formula, where 0 < n ≤ 0.6, 0 ≤ x ≤ 6, 0 ≤ y ≤ 6, x + y ≤ 6, and M is selected from one or more of V, Cr, Mn, Fe, Co, or Ni, etc. Further, M is, for example, selected from Fe. The value range of n is, for example, 0.01 ≤ n ≤ 0.5. Further, n is, for example, 0.35. The halide solid electrolyte core does not contain expensive rare earth metals, which can significantly reduce costs. Moreover, the halide solid electrolyte core uses elements such as iron as doping elements, and the isovalent substitution of Fe in the crystal lattice can improve the ionic conductivity of the halide solid electrolyte core. The inorganic halide solid electrolyte core has a relatively wide electrochemical window, which can better be compatible with the cathode active material and improve the interfacial performance between the solid electrolyte membrane and the electrode sheet. The doping amount of the M element is controlled to ensure the performance of the halide solid electrolyte core itself and simultaneously improve the cycling performance of the lithium-ion battery. If the doping amount is too low, the improvement effect of the halide solid electrolyte core itself is not obvious and the cycling performance is poor. If the doping amount of M is too large, excessive doping will cause excessive lattice distortion and damage the original crystal structure, which may lead to a decrease in the structural stability of the material, thereby a decrease in the chemical stability and ionic conductivity of the halide solid electrolyte core and a decrease in the cycling performance of the lithium-ion battery.

[0031] ​​In one embodiment of the present invention, the thickness of the hydrophobic layer is, for example, 1 nm to 100 nm, and the thickness of the hydrophobic layer is tested, for example, by scanning electron microscopy or transmission electron microscopy. When the hydrophobic layer is too thin, it is not enough to improve the air stability of the halide solid electrolyte core. When the hydrophobic layer is too thick, the outer hydrophobic alkyl surface will greatly prevent the transmission of lithium ions, and the conductivity of the halide solid electrolyte will be seriously reduced, thereby affecting the battery performance. By forming a hydrophobic layer on the halide solid electrolyte core, the DHP molecules are first adsorbed on the surface of the halide solid electrolyte core, and then the halide solid electrolyte core and the inner layer of the DHP molecules produce a condensation reaction to form an O=POLi covalent bond, forming a battery with an outer hydrophobic alkyl surface and an inner layer with high Li + The hydrophobic layer of the O=POLi covalent bond with a transmission coefficient. The hydrophobic layer can greatly improve the air stability of the halide solid electrolyte without significantly reducing the ionic conductivity of the halide solid electrolyte. In one embodiment of the present invention, after the halide solid electrolyte with a hydrophobic layer is exposed to a dry room at -40°C for 24 hours, the ionic conductivity retention rate is, for example, 38% to 78%. Furthermore, by controlling the doping amount of the M element in the chemical formula of the halide solid electrolyte core and the thickness of the hydrophobic layer, the ionic conductivity retention rate of the halide solid electrolyte after being exposed to a dry room at -40°C for 24 hours is, for example, 67% to 78%, which can greatly improve the air stability of the halide solid electrolyte.

[0032] The present invention also proposes a method for preparing a halide solid electrolyte, which includes at least the following steps: adding a hydrophobic agent to a solvent to prepare a modified solution; soaking the halide solid electrolyte core in the modified solution at a preset temperature for a first time; taking out the soaked halide solid electrolyte core and drying it under vacuum conditions.

[0033] In one embodiment of the present invention, the solvent is selected from one or more of toluene, chlorobenzene, xylene, n-heptane, n-decane, n-hexane, glycol dimethyl ether, 1,2-ethylenediamine, ethyl acetate, benzyl acetate or butyl butyrate, and the hydrophobic agent includes, for example, dihexadecyl phosphate, and the concentration of the hydrophobic agent in the modified solution is, for example, 0.01 mol / L to 0.5 mol / L.

[0034] In one embodiment of the present invention, the halide solid electrolyte core is obtained according to the following method: According to the chemical formula of the halide solid electrolyte core Li 2+n Zr 1-n M n Cl 6-x-y Br x I y, after the Li source, Zr source, M source, Cl source, Br source and I source are mixed evenly according to stoichiometric ratio, they are added to a ball milling jar, and the halide solid electrolyte core material is obtained after ball milling. Wherein, the Li source is selected from one or more of LiCl, LiBr, LiI or Li, the Zr source is selected from Zr halide, the M source is selected from M halide, etc., and the Cl source, Br source and I source in the chemical formula are respectively derived from at least one of LiCl, LiBr, LiI, Zr halide or M halide. After the raw materials are mixed evenly, they are placed in a ball milling jar and ball milled under an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1000 rpm, and the ball milling time is, for example, 24h to 48h, to obtain the halide solid electrolyte core after ball milling.

[0035] In one embodiment of the present invention, the halide solid electrolyte core is immersed in a modified solution at a preset temperature for a first time, wherein the preset temperature is, for example, 0 to 60°C and the first time is, for example, 0.1h to 10h, to control the thickness of the formed hydrophobic layer. The halide solid electrolyte core after immersion is taken out and dried under vacuum conditions, wherein the drying temperature is, for example, 25°C to 300°C and the drying time is, for example, 0.1h to 24h. A uniformly coated hydrophobic layer can be formed on the surface of the halide solid electrolyte core material by a simple immersion method, and the preparation process is simple and the cost is low.

[0036] The present invention also proposes an all-solid-state lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane comprises the above-mentioned halide solid electrolyte to improve the cycle performance of the all-solid-state lithium-ion battery. In one embodiment of the present invention, the solid electrolyte membrane is obtained by, for example, cold pressing the above-mentioned halide solid electrolyte at a pressure of 300MPa to 400MPa, and the thickness of the solid electrolyte membrane is, for example, 100μm to 500μm. In the present invention, the all-solid-state lithium-ion battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery. The present invention does not impose any specific restrictions on the type and type of the all-solid-state lithium-ion battery.

[0037] In one embodiment of the present invention, the positive electrode sheet includes, for example, a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel, or carbon. In addition to foil, the positive electrode current collector may also be in the form of a film, mesh, porous, foam, or non-woven fabric, among other forms, or a combination thereof. The thickness of the positive electrode current collector is, for example, 8 μm to 15 μm.

[0038] In one embodiment of the present invention, the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a positive electrode conductor, and a positive electrode binder, wherein the positive electrode active material is, for example, selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO), or lithium nickel cobalt aluminum oxide (NCA), the positive electrode electrolyte is, for example, a halide solid electrolyte, the positive electrode conductor is, for example, selected from at least one of graphite, graphene, conductive carbon black (Super P), nanocarbon fiber (Vapor-grown Carbon Fiber, VGCF), or carbon nanotubes, and the positive electrode binder is, for example, selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), and the like. Methacrylate, PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane (PU), polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer (EPDM), styrene-butadiene rubber, fluororubber (Fluororubber), β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (Ethylene-chlorotrifluoroethylene) Copolymer (ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) or polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE).

[0039] In one embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is, for example, the above-mentioned halide solid electrolyte, the positive electrode conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the positive electrode binder is, for example, PTFE. After the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder are uniformly mixed, for example, in a mass ratio of 69:29:1:1, they are compounded with aluminum foil by dry pressing to obtain a positive electrode sheet. The present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder, and can be selected according to actual needs, and the positive electrode current collector can be not provided as needed.

[0040] In one embodiment of the present invention, the negative electrode plate is selected from at least one of a lithium metal plate, an indium metal plate, or a lithium-indium alloy plate. In another embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one side of the negative electrode current collector. The negative electrode current collector may be, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector, and may have a thickness of, for example, 8 μm to 15 μm.

[0041] In one embodiment of the present invention, the negative electrode active layer includes, for example, a negative electrode active material, a negative electrode electrolyte, a negative electrode conductive agent, and a negative electrode binder. The negative electrode active material is selected from at least one of a graphite material or a silicon-containing material. The silicon-containing material is, for example, at least one of a silicon material, a silicon oxide material, or a silicon-carbon material. The negative electrode electrolyte is, for example, a halide solid electrolyte. The negative electrode conductive agent is selected from at least one of graphite, graphene, Super P, VGCF, or carbon nanotubes. The negative electrode binder is selected from at least one of PVDF, CMC, SBR, PVP, PMMA, PAN, PAA, PU, ​​PVA, Alg, EPDM, styrene-butadiene rubber, fluororubber, β-CDp, LA132, PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, PVDF-HFP, or PVDF-CTFE.

[0042] In one embodiment of the present invention, the negative electrode current collector is, for example, copper foil, the negative electrode active material is, for example, a mixture of silicon oxide material and graphite, and the ratio of silicon oxide material to graphite is, for example, 5:95, the negative electrode electrolyte is, for example, the above-mentioned halide solid electrolyte, the negative electrode conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the negative electrode binder is, for example, SBR. After the negative electrode active material, the negative electrode electrolyte, the negative electrode conductive agent and the negative electrode binder are uniformly mixed in a mass ratio of, for example, 72:22:3:3, they are compounded with copper foil by dry pressing to obtain a negative electrode sheet. The present invention does not limit the mass ratio of the negative electrode active material, the negative electrode electrolyte, the negative electrode conductive agent and the negative electrode binder, and they can be selected according to actual needs, and the negative electrode current collector can be omitted as needed.

[0043] In one embodiment of the present invention, the aforementioned positive electrode sheet, solid electrolyte membrane, and negative electrode sheet are sequentially placed and pressed and sealed to obtain an all-solid-state lithium-ion battery. The assembly process of the all-solid-state lithium-ion battery is completed in an inert atmosphere glove box.

[0044] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0045] Example 1

[0046] Preparation of solid electrolyte membrane: Under argon atmosphere, 1.35 mol of LiCl, 0.5 mol of LiBr, 0.5 mol of LiI, 0.65 mol of ZrCl4 and 0.35 mol of FeCl3 were added into a ball mill and milled at 600 rpm for 40 h to obtain a solid electrolyte membrane with the chemical formula Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The halide solid electrolyte core was prepared by adding DHP to a xylene solution to create a 0.01 mol / L DHP solution. The halide solid electrolyte core was then immersed in the DHP solution at 25°C for 1 hour. After immersion, the core was filtered and then dried in a vacuum oven at 80°C for 12 hours to remove any residual solvent, yielding a moisture-resistant halide solid electrolyte with a DHP hydrophobic layer. This was then cold-pressed at 350 MPa to obtain a 300 μm thick solid electrolyte membrane.

[0047] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1O2, a positive electrode conductive agent, the aforementioned halide solid electrolyte, and PTFE are mixed uniformly in a mass ratio of 69:29:1:1, laminated with aluminum foil by dry pressing, and cut into discs with a diameter of 10 mm to obtain a positive electrode sheet. The positive electrode conductive agent includes Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1.

[0048] Selection of negative electrode sheet: Select lithium-indium alloy sheet and cut it into discs with a diameter of 10 mm to obtain the negative electrode sheet.

[0049] All-solid-state lithium-ion battery assembly: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet prepared above are stacked in sequence, pressed and sealed, and assembled into an all-solid-state lithium-ion battery.

[0050] Example 2

[0051] The concentration of the DHP solution was 0.05 mol / L, and other operations were consistent with those in Example 1.

[0052] Example 3

[0053] The concentration of the DHP solution was 0.1 mol / L, and other operations were consistent with those in Example 1.

[0054] Example 4

[0055] The concentration of the DHP solution was 0.2 mol / L, and other operations were consistent with those in Example 1.

[0056] Example 5

[0057] The concentration of the DHP solution was 0.5 mol / L, and other operations were consistent with those in Example 1.

[0058] Example 6

[0059] The electrolyte was immersed in the DHP solution for 0.1 h, and other operations were consistent with those in Example 1.

[0060] Example 7

[0061] The electrolyte was immersed in the DHP solution for 0.5 h, and other operations were consistent with those in Example 1.

[0062] Example 8

[0063] The electrolyte was immersed in the DHP solution for 5 h, and other operations were consistent with those in Example 1.

[0064] Example 9

[0065] The electrolyte was immersed in the DHP solution for 10 h, and other operations were the same as those in Example 1.

[0066] Example 10

[0067] The chemical formula of the halide solid electrolyte core prepared by 1.1 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.9 mol ZrCl4 and 0.1 mol FeCl3 is Li 2.1 Zr 0.9 Fe 0.1 Cl5Br 0.5 I 0.5 , other operations remain the same as in Example 3.

[0068] Example 11

[0069] The chemical formula of the halide solid electrolyte core prepared by 2mol of 1.2mol LiCl, 0.5mol LiBr, 0.5mol LiI, 0.8mol ZrCl4 and 0.2mol FeCl3 is Li 2.2 Zr 0.8 Fe 0.2 Cl5Br 0.5 I 0.5 , other operations remain the same as in Example 3.

[0070] Example 12

[0071] The chemical formula of the halide solid electrolyte core prepared by 1.6 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.4 mol ZrCl4 and 0.6 mol FeCl3 is Li 2.6 Zr 0.4 Fe 0.6 Cl5Br 0.5 I 0.5 , other operations remain the same as in Example 3.

[0072] Comparative Example 1

[0073] The chemical formula of the halide solid electrolyte core prepared by 1 mol of LiCl, 0.5 mol of LiBr, 0.5 mol of LiI and 1 mol of ZrCl4 is Li2ZrCl5Br 0.5 I 0.5 , other operations remain the same as in Example 3.

[0074] Comparative Example 2

[0075] The core of the halide solid electrolyte Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5Add the solution to a xylene solution and soak for 1 hour. After soaking, filter the solution and dry it in a vacuum oven at 80°C for 12 hours to remove any residual solvent, thereby obtaining a halide solid electrolyte. Cold press the solution at a pressure of 350 MPa to obtain a 300 μm thick solid electrolyte membrane. All other procedures were the same as in Example 1.

[0076] Comparative Example 3

[0077] The concentration of the DHP solution was 1 mol / L, and other operations were consistent with those in Example 1.

[0078] In Examples 1-12 and Comparative Examples 1-3 of the present invention, different halide solid electrolyte cores and preparation methods are used to obtain halide solid electrolytes and all-solid-state lithium-ion batteries. Some preparation conditions and performances of halide solid electrolytes are shown in Table 1. Under a 25°C environment, the above-prepared all-solid-state lithium-ion battery is subjected to long-cycle charge and discharge, its discharge capacity is measured, and the energy density is calculated. Among them, the operating voltage range of the battery test is 1.9V-3.7V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as 1C discharge capacity. When the battery capacity reaches 80% (80% State of Health, 80% SOH) of the first cycle capacity, the test is terminated to obtain the number of cycles at room temperature. The test results are shown in Table 2.

[0079] Table 1. Preparation conditions and properties of some halide solid electrolytes in Examples 1-12 and Comparative Examples 1-3

[0080]

[0081] Table 2 Performance test results of all-solid-state lithium-ion batteries in Examples 1-12 and Comparative Examples 1-3

[0082]

[0083] Please refer to Table 1 and Table 2. It can be seen from the comparison between Examples 1-5 and Comparative Examples 2-3 that as the concentration of the DHP solution increases and the immersion time is the same, the thickness of the hydrophobic layer becomes larger and larger, the ion conductivity retention rate of the halide solid electrolyte after being exposed to a -40°C dry room for 24 hours gradually increases, and the cycle performance of the all-solid-state lithium-ion battery gradually increases and then gradually decreases. This is because the thicker the hydrophobic layer, the better the air stability of the halide solid electrolyte, the better the chemical stability and ion conductivity of the halide solid electrolyte, the appearance of the hydrophobic layer can reduce the interface side reaction between the electrolyte and the positive / negative active material, and the inner layer O=POLi covalent bond can improve the Li + However, when the hydrophobic layer is too thick, the hydrophobic alkyl surface of the outer layer will greatly hinder the transmission of lithium ions, and the conductivity of the electrolyte will be seriously reduced, thereby affecting the battery performance.

[0084] As shown in Table 1 and Table 2, by comparing Example 3 and Examples 6-9, it can be seen that when the concentration of the DHP solution is the same, as the immersion time of the halide solid electrolyte core in the DHP solution increases, the thickness of the hydrophobic layer becomes larger and larger, and the ionic conductivity retention rate of the halide solid electrolyte after being exposed to a -40°C dry room for 24 hours gradually increases. When the thickness of the hydrophobic layer is greater than 60 nm, the ionic conductivity retention rate tends to be stable. At the same time, the cycle performance of the all-solid-state lithium-ion battery gradually increases and then gradually decreases.

[0085] See also Figure 1 As shown, at a current density of 1C, the all-solid-state lithium-ion battery in Example 3 still has an energy storage capacity of about 135 mAh / g after 876 cycles, indicating that the halide solid electrolyte has excellent reaction kinetics and cycle stability, and has good hydrophobicity. The obtained solid electrolyte membrane has a good gain effect on the cycle stability and reaction activity specific capacity of the battery. The all-solid-state lithium-ion battery has excellent specific capacity, rate performance and cycle life.

[0086] Refer to Table 1 and Table 2. Comparative Example 3 and Example 10-12 show that as the doping amount of Fe element in the halide solid electrolyte core increases, the ionic conductivity of the halide solid electrolyte after being exposed to a -40°C dry room for 24h remains first increased and then decreased, and the cycle performance of the all-solid-state lithium ion battery gradually increases and then gradually decreases. This is because, when the M doping amount in the halide solid electrolyte core is too low, the performance improvement effect of the halide solid electrolyte core itself is not obvious, and the cycle performance is poor. When the M doping amount in the halide solid electrolyte core is within a suitable range, with a hydrophobic layer, the chemical stability and ionic conductivity of the halide solid electrolyte can be improved, thereby improving the cycle performance of the all-solid-state lithium ion battery. When the M doping amount in the halide solid electrolyte core is too large, excessive doping can cause excessive lattice distortion, destroying the original crystal structure, which may cause the structural stability of the material to decrease, thereby reducing the chemical stability and ionic conductivity of the halide solid electrolyte and reducing the cycle performance of the all-solid-state lithium ion battery.

[0087] The present invention also provides an electronic device, which includes at least one of the above-mentioned all-solid-state lithium-ion batteries, and the all-solid-state lithium-ion battery is used to provide electrical energy. The electronic device may be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, which may be a pure electric vehicle, a hybrid electric vehicle, or an extended-range vehicle. The spacecraft includes airplanes, rockets, space shuttles, and spacecrafts, and the electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys. The electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools, and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers. The electronic device includes the above-mentioned all-solid-state lithium-ion battery, and therefore includes the advantages of the above-mentioned all-solid-state lithium-ion battery, which will not be elaborated on here.

[0088] In summary, the present invention proposes a halide solid electrolyte and its preparation method and application. By introducing the M element into the core of the halide solid electrolyte, the ionic conductivity of the halide solid electrolyte can be improved, the interface performance between the solid electrolyte membrane and the electrode can be improved, and the cost can be reduced. By introducing a dense hydrophobic layer on the surface of the halide solid electrolyte core, the contact between water molecules and the halide solid electrolyte core can be blocked, thereby significantly improving the air stability of the halide solid electrolyte. It is possible to form a halide solid electrolyte with an outer hydrophobic alkyl surface and an inner layer with high Li + The hydrophobic layer has good chemical stability and ion conductivity, which can greatly improve the stability of the halide solid electrolyte to air without significantly reducing the ion conductivity of the halide solid electrolyte, thereby improving the cycle performance of all-solid-state lithium-ion batteries. A simple immersion method can achieve a uniform hydrophobic layer coating on the surface of the halide solid electrolyte, which is simple to process and low in cost.

[0089] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to the technical solutions formed by the specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as the technical solutions formed by the mutual replacement of the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0090] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A halide solid electrolyte, characterized in that: At least: Halide solid electrolyte core; as well as A hydrophobic layer is uniformly coated on the halide solid electrolyte core, and the hydrophobic layer comprises dihexadecyl phosphate.

2. The halide solid electrolyte according to claim 1, characterized in that The thickness of the hydrophobic layer is 1 nm to 100 nm.

3. The halide solid electrolyte according to claim 1, characterized in that The chemical formula of the halide solid electrolyte core is Li 2+n Zr 1-n M n Cl 6-x-y Br x I y , where 0 < n ≤ 0.6, 0 ≤ x ≤ 6, 0 ≤ y ≤ 6, x + y ≤ 6; M is selected from one or more of V, Cr, Mn, Fe, Co or Ni.

4. The halide solid electrolyte according to claim 3, characterized in that M is selected as Fe, and the value range of n is 0.01≤n≤0.

5.

5. A method for preparing the halide solid electrolyte according to any one of claims 1 to 4, characterized in that: At least the following steps are included: adding a hydrophobic agent into a solvent to prepare a modified solution; soaking the halide solid electrolyte in the modified solution at a preset temperature for a first time; as well as The halide solid electrolyte is taken out after soaking and dried under vacuum conditions.

6. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The preset temperature is 0-60° C., and the first time is 0.1 h-10 h.

7. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The solvent is selected from one or more of toluene, chlorobenzene, xylene, n-heptane, n-decane, n-hexane, glycol dimethyl ether, 1,2-ethylenediamine, ethyl acetate, benzyl acetate or butyl butyrate, the hydrophobic agent includes dihexadecyl phosphate, and the concentration of the hydrophobic agent in the modified solution is 0.01 mol / L to 0.5 mol / L.

8. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The drying conditions include: a drying temperature of 25° C. to 300° C. and a drying time of 0.1 h to 24 h.

9. An all-solid-state lithium-ion battery, characterized in that: include: Positive electrode; Negative electrode; A solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane comprises the halide solid electrolyte according to any one of claims 1 to 4.

10. An electronic device, characterized in that: Including the all-solid-state lithium-ion battery as described in claim 9.

Citation Information

Patent Citations

  • Sulfide solid electrolyte material, preparation method thereof and solid-state battery

    CN111129579A

  • Super-hydrophobic material capable of conducting lithium ions as well as preparation method and application thereof

    CN112701345A

  • Sulfide solid electrolyte material and preparation method thereof

    CN115275332A

  • Modified sulfide solid electrolyte, preparation method thereof and all-solid-state battery

    CN116505059A

  • All-solid-state lithium ion battery

    CN117154202A

Cited By

  • Solid electrolyte, preparation method thereof and lithium battery

    CN121307171A

  • Lithium ion oxyhalide solid electrolyte composite membrane

    CN122267272A